Laser all‐ceramic crown removal—a laboratory proof‐of‐principle study—Phase 2 crown debonding time. Issue 8 (13th August 2014) - Rechmann, Peter; Buu, Natalie C.H.; Rechmann, Beate M.T.; Finzen, Frederick C.
<x xml:space="preserve">Abstract</x> Background and Objectives The removal of all‐ceramic crowns is a time consuming procedure in the dental office. Little research has been done in alternative removal techniques for all‐ceramic crowns. The objective of the second phase of this proof‐of‐principle laboratory pilot study was to evaluate whether Ivoclar Vivadent all‐ceramic crowns can be efficiently removed from natural teeth without damage to the underlying tooth structure using an Erbium laser. Study Design/Materials and Methods The ceramic materials used were IPS E.max CAD Lithium‐disilicate (LS2) (E.max CAD) and IPS E.max ZirCAD Zirconium‐oxide (ZrO2) (ZirCAD) (Ivoclar, Vivadent, Liechtenstein). Molars, either as stand‐alone teeth or placed in an artificial row of teeth, were prepared to receive all‐ceramic crowns. Copings and full contour crowns with either featheredge or regular margins were produced. The all‐ceramic crowns were bonded to the teeth with Ivoclar Multilink Automix. The time for Er:YAG laser debonding of each crown was then measured. The Er:YAG (LiteTouch, Syneron, Yokneam, Israel) was used with an 1, 100 µm diameter fiber tip with energies up to 600 mJ per pulse (wavelength 2, 940 nm, 10 Hz repetition rate, pulse duration 100 µs at 126 mJ/pulse, and 400 µs at 590 mJ/pulse). The irradiation was applied at a distance of 10 mm from the crown surface following a defined pattern. Air‐water spray was applied to the crowns at a rate of 67 ml/minute. Results All of the all‐ceramic crowns were successfully debonded with the laser. On average, an all‐ceramic E.max CAD crown was debonded in 190 ± 92 seconds (average ± SD). The debonding time for ZirCAD featheredge crowns was 226 ± 105 seconds and for ZirCAD crowns with regular margins it was 312 ± 102 seconds. No crowns fractured and no damage to the underlying dentin was detected. The bonding cement deteriorated due to the Er:YAG irradiation. Additionally, no carbonization at the dentin/cement interface was observed. Conclusion Er:YAG laser energy can successfully be used to efficiently debond all‐ceramic full contour crowns from natural teeth without damage to the underlying tooth structure. Lasers Surg. Med. 46:636–643, 2014. © 2014 Wiley Periodicals, Inc.